(untitled) (Research, Society and Development, 2024)
The action of botulinum toxins is the result of their powerful ability to inhibit the release of neurotransmitters. In this sense, botulinum toxins have a wide range of indications, both cosmetic and therapeutic. The aim of this study was to carry out a bibliographical survey on the use of botulinum toxin Type A (BoNT/A) in facial aesthetics and emotion processing. To this end, we evaluated randomized clinical trials (RCTs) that analyzed the effects of BoNT/A on patients with mood disorders, with an emphasis on depression. The search was carried out in the PubMed, SCIELO, Web of Science and LILACS databases, using DeCS/MeSH descriptors, and included articles published in Portuguese and English between 2003 and 2023. After applying the criteria, 13 articles were selected for analysis. Overall, BoNT/A was shown to be an alternative that significantly improved facial signs of depression when compared to placebo in the studies carried out. In most of the RCTs, BoNT/A was applied to the mimic muscles of the upper third of the face, in the glabellar area, which was related to the improvement of mood disorders targeted by facial feedback. Thus, clinical evidence suggests that the management of emotional disorders includes the use of botulinum toxin therapy.